2013
DOI: 10.1111/pcn.12089
|View full text |Cite
|
Sign up to set email alerts
|

Role of immunological factors in the pathophysiology and diagnosis of bipolar disorder: Comparison with schizophrenia

Abstract: Several lines of evidence point to the key role of neurobiological mechanisms and shared genetic background in schizophrenia and bipolar disorder. For both disorders, neurodevelopmental and neurodegenerative processes have been postulated to be relevant for the pathogenesis as well as dysregulation of immuno-inflammatory pathways. Inflammation is a complex biological response to harmful stimuli and it is mediated by cytokines cascades, cellular immune responses, oxidative factors and hormone regulation. Cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 164 publications
(434 reference statements)
2
66
0
1
Order By: Relevance
“…Our finding is consistent with previous studies indicating similarities and differences in the immune system in individuals with schizophrenia and bipolar disorder based on genetic, neuropathological, and gene expression studies (Altamura et al, 2014;Mamdani et al, 2013). The further elucidation of the similarities and differences in the immune system activity of individuals with schizophrenia and bipolar disorder would represent a major step in terms of elucidating the role of immune alteration in the pathogenesis of these disorders.…”
Section: Discussionsupporting
confidence: 95%
“…Our finding is consistent with previous studies indicating similarities and differences in the immune system in individuals with schizophrenia and bipolar disorder based on genetic, neuropathological, and gene expression studies (Altamura et al, 2014;Mamdani et al, 2013). The further elucidation of the similarities and differences in the immune system activity of individuals with schizophrenia and bipolar disorder would represent a major step in terms of elucidating the role of immune alteration in the pathogenesis of these disorders.…”
Section: Discussionsupporting
confidence: 95%
“…This complex condition is often exacerbated by the presence of one or more comorbid conditions, in addition to a number of clinical factors such long duration of illness (Altamura et al, 2015;Altamura et al, 2010). While BD, schizophrenia spectrum disorders (SSD) and autism spectrum disorders (ASD) are considered distinct conditions, there is evidence for an overlap between BD and SSD (Altamura, Buoli, & Pozzoli, 2014;Carroll & Owen, 2009;Moller, 2003), as well as between ASD and BD (Carroll & Owen, 2009;Stahlberg, Soderstrom, Rastam, & Gillberg, 2004). Indeed, BD has a number of genetic, symptomatological and epidemiological overlaps with SSD (Laursen, Agerbo, & Pedersen, 2009;Lichtenstein et al, 2009;Murray et al, 2004), and psychosis has been recognised as an important dimension in the psychopathology of BD (van Os & Kapur, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some data indicate pro-inflammatory cytokines to be responsible for cognitive disturbances in schizophrenia [77]. In a doubleblind placebo-controlled study, 50 schizophrenia patients on risperidone (2-6 mg/day) treatment showed cognitive improvement by celecoxib add-on therapy, but without reaching statistical significance [78].…”
Section: Celecoxibmentioning
confidence: 98%